Aneurysm of anterior inferior cerebellar artery-posterior inferior cerebellar artery variant - Ansari, Khursheed; Menon, Girish; Nair, Suresh; Abraham, Mathew (Asian Journal of Neurosurgery, 2018)
Aneurysms arising from anterior inferior cerebellar artery-posterior inferior cerebellar artery (AICA-PICA) variant are extremely rare. They usually present with subarachnoid hemorrhage. This is probably the second case report of a large thrombosed AICA-PICA variant aneurysm presenting as a cerebellopontine angle mass lesion with cranial nerve palsy, managed successfully by surgical clipping.
Keywords: Aneurysm; anterior inferior cerebellar artery; clipping; posterior inferior cerebellar artery